2006
DOI: 10.1637/7512-020606r.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Typing of Chicken and Turkey Astroviruses Circulating in the United States: Implications for Diagnostics

Abstract: Avian astroviruses were detected by reverse transcriptase and polymerase chain reaction in intestinal contents collected from commercial chickens and turkeys from throughout the United States from 2003 through 2005. Astroviruses were detected in birds from both healthy and poorly performing flocks with or without enteric disease. Phylogenetic analysis was performed with sequence data from the polymerase (ORF-1b) genes of 41 turkey-origin astroviruses and 23 chicken-origin astroviruses. All currently available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 46 publications
6
98
1
Order By: Relevance
“…CAstVs were also detected in a recent study by Pantin-Jackwood et al (2006), who applied the Method 2 RT-PCR to faeces and gut content samples from chickens and turkeys obtained from problem and nonproblem US flocks. Nucleotide identities between 85.1% and 98.4% and amino acid identities between 92.4% and 100% were observed when 13 CAstV ORF 1b amplicon sequences were compared.…”
Section: Discussionmentioning
confidence: 96%
“…CAstVs were also detected in a recent study by Pantin-Jackwood et al (2006), who applied the Method 2 RT-PCR to faeces and gut content samples from chickens and turkeys obtained from problem and nonproblem US flocks. Nucleotide identities between 85.1% and 98.4% and amino acid identities between 92.4% and 100% were observed when 13 CAstV ORF 1b amplicon sequences were compared.…”
Section: Discussionmentioning
confidence: 96%
“…The viral RNA polymerase is considered to be one of the more conserved regions in the ANV genome. Nucleotide identities of 86-99% were found between the polymerase gene of ANV isolates in the United States (Pantin-Jackwood, 2006). The capsid gene on the other hand is the most variable with the capsid gene of European and Asian isolates having nucleotide identities of 56-100% (Todd et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Besides affecting mostly young mammals, astroviruses became a common finding in poultry after they were first reported in 1980 in turkey faeces (McNulty et al, 1980;Koci & Schultz-Cherry, 2002). Avian astroviruses are linked to poult enteritis and mortality syndrome (PEMS) in turkeys, runting and stunting syndrome (RSS) in chickens, fatal hepatitis in ducklings and enteritis in guinea fowl (Gough et al, 1984;Baxendale & Mebatsion, 2004;Catolli et al, 2005;Pantin-Jackwood et al, 2006;Spackman et al, 2010). They are classified as turkey astrovirus, chicken astrovirus, avian nephritis virus (ANV) and duck astrovirus (DAstV) (Wilcocks et al, 1992;Koci & Schultz-Cherry, 2002;Baxendale & Mebatsion, 2004;Fu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pantin-Jackwood et al (2006) identified and sequenced ANV for the first time from turkeys affected with PEMS; however, the role of ANV has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation